1984
DOI: 10.1017/s0016672300026094
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the dietary sucrose modulation of enzyme activities inDrosophila melanogaster

Abstract: Genetic variation in the modulating effect of dietary sucrose was assessed in Drosophila melanogaster by examining 27 chromosome substitution lines coisogenic for the X and second chromosomes and possessing different third isogenic chromosomes derived from natural populations. An increase in the concentration of sucrose from 01 % to 5 % in modified Sang's medium C significantly altered the activities of 11 of 15 enzyme activities in third instar larvae, indicating that dietary sucrose modulates many, but not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Geer et a!. (1979a, b) and Geer and Laurie-Ahlberg (1984) have shown that adaptation to dietary sucrose in D. melanogaster increases activity in the enzyme G6PD. As shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…Geer et a!. (1979a, b) and Geer and Laurie-Ahlberg (1984) have shown that adaptation to dietary sucrose in D. melanogaster increases activity in the enzyme G6PD. As shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…This explanation is, however, likely an oversimplification. Apparently compensatory changes in enzyme activity have been documented between the oxidative pentose shunt enzymes and MEN; extreme reduction in MEN activity is associated with an increase in G6PD and 6PGD activity Geer and Laurie-Ahlberg 1984). However, no such compensation has been found between IDH and MEN; reduction in MEN is associated with reduction, not increase, in IDH activity Geer and Laurie-Ahlberg 1984).…”
mentioning
confidence: 99%
“…Apparently compensatory changes in enzyme activity have been documented between the oxidative pentose shunt enzymes and MEN; extreme reduction in MEN activity is associated with an increase in G6PD and 6PGD activity Geer and Laurie-Ahlberg 1984). However, no such compensation has been found between IDH and MEN; reduction in MEN is associated with reduction, not increase, in IDH activity Geer and Laurie-Ahlberg 1984). Similarly, an increase in dietary carbohydrate increases G6PD, 6PGD, and MEN activity, but decreases IDH activity (Geer et al 1978;Geer and Laurie-Ahlberg 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the major antioxidant systems are dependent on the availability of NADPH that is principally produced by G 6 PD. Adaptation to dietary sucrose in D. melanogaster increases activity in the enzyme [54,55]. G 6 PD activity has studied in different genetic stocks of D. melanogaster to correlate lifespan [56].…”
Section: G 6 Pd Assaymentioning
confidence: 99%